Lipopolysaccharide sensitizes the therapeutic response of breast cancer to IAP antagonist - Liu, Xin; Yao, Jimmy J.; Chen, Zhongxuan; Lei, Wei; Duan, Rong; Yao, Zhenqiang (Frontiers in Immunology, 2022)
Inhibitor of apoptosis proteins (IAP) is a class of E3 ubiquitin ligases, functioning to support cancer survival and growth. Many small-molecule IAP antagonists have been developed, aiming to degrade IAP proteins to kill cancer. We have evaluated the effect of lipopolysaccharide (LPS), a component of bacterial outer membrane, on IAP antagonists in treating breast cancer in a mouse model to guide future clinical trials. We show that LPS promotes IAP antagonist-induced regression of triple negative breast cancer (TNBC) from MDA-MB-231 cells in immunodeficient mice. An IAP antagonist, such as SM-164, AT-406 and BV6, alone does not kill MDA-MB-231 cells but allows LPS to induce cancer cell apoptosis rapidly. The apoptosis caused by LPS plus SM-164 is blocked by TLR4 or MyD88 inhibitor, which inhibits LPS-induced TNF production by the cancer cells. Consistent with this, MDA-MB-231 cell apoptosis induced by LPS plus SM-164 is also blocked by TNF inhibitor. LPS alone does not kill MDA-MB-231 cells because it markedly increases the protein level of cIAP1/2, which is directly associated with and stabilized by MyD88, an adaptor protein of TLR4. ER+ MCF7 breast cancer cells expressing low levels of cIAP1/2 are undergone apoptosis in response to SM-164 combined with TNF but not with LPS. Furthermore, TNF but not LPS alone inhibits MCF7 cell growth in vitro. Consistent with these, LPS combined with SM-164, but not either of them alone, causes regression of ER+ breast cancer from MCF7 cells in immunodeficient mice. In summary, LPS sensitizes the therapeutic response of both triple negative and ER+ breast cancer to IAP antagonist therapy by inducing rapid apoptosis of the cancer cells through TLR4- and MyD88- mediated production of TNF. We conclude that antibiotics that can reduce microbiota derived LPS should not be used together with an IAP antagonist for cancer therapy.